Monodentate palladium(0)–[60]fullerene complexes of diphosphine ligands as efficient and sustainable nanocatalysts for the Mizoroki–Heck coupling reaction of aryl chlorides. (9th August 2017) - Sabounchei, Seyyed Javad; Hosseinzadeh, Marjan; Zarepour-jevinani, Morteza; Ghanbari, Bahram
Abstract : The present article combines fullerene chemistry with phosphine-based Pd catalytic systems to report new palladium(0)–[60]fullerenes as heterogeneous nanocatalysts for C–C bond transformations of aryl chlorides. Abstract : Two mononuclear coordination complexes of fullerene[60] with Pd(dba)2 (dba = dibenzylideneacetone), [(η 2 -C60 )Pd(Ph2 P(CH2 )2 PPh2 C(H)C(O)R)2 ] (R = C10 H7 (1 ), C6 H4 Cl (2 )), have been prepared using a simple procedure to explore new directions in palladium catalysis and nanocarbon chemistry. The palladium(0)–[60]fullerene complexes incorporating unsymmetrical phosphorus ylides have been characterized by 1 H, 13 C and 31 P NMR spectroscopic methods and other conventional techniques such as IR, TGA, SEM, ICP-OES, EDX and TEM analysis. Attributed to the enhanced dispersity and uniform size of the Pd nanoparticles with phosphine-functionalized fullerenes, the prepared catalysts exhibited comparable catalytic activity to those reported for the Mizoroki–Heck coupling reaction of aryl chlorides. Because of their abundance and low cost, aryl chlorides are the most desirable substrates from an industrial point of view in Csp 2 –Csp 2 coupling reactions. Furthermore, overall bonding modes in the palladafullerenes of bifunctional diphosphine-based ligands were investigated by spectroscopic analysis and theoretical calculations. DFT studies of geometry-optimized monodentate and bidentate structures for1 were calculated at the B3LYP/LANL2MB level of theory to understand the origin of the observed coordination modes.